A Study to Assess the Effectiveness of a Self-Instructional Module on Knowledge Regarding the Use of a Communication Board in Communicating with Patients on Mechanical Ventilation Among Staff Nurses Working in a Selected Hospital at Bangalore - Sheela A J Williams; Sowjanya P (RGUHS Journal of Nursing Sciences)
Background A communication board is used in intensive care units ICUs to communicate with patients on mechanical ventilation. It facilitates transfer of messages between patients and staff nurses. This study attempted to assess the effectiveness of a self-instructional module SIM on knowledge of staff nurses regarding the use of a communication board for communicating with patients on mechanical ventilation at a selected hospital in Bangalore.Objective To assess the effectiveness of a self-instructional module on knowledge regarding the use of a communication board among staff nurses working at a selected hospital in Bangalore.Methods A pre-experimental study included 30 staff nurses working at a selected hospital in Bengaluru. Demographic details of all the staff nurses were collected. A structured knowledge questionnaire was used for collecting baseline data from the staff nurses on their knowledge about the communication board for communicating with patients on mechanical ventilation. The intervention was given with the aid of a SIM. The results were described using descriptive and inferential statistics.Results The pre-test results showed that 12 40 respondents had inadequate levels of knowledge 18 60 demonstrated moderate levels of knowledge and none of them had adequate knowledge. In the post-test 25 83.3 had adequate levels of knowledge 5 16.7 had moderate levels of knowledge and none of the staff nurses had inadequate knowledge. The mean pre-test knowledge score percentage was 57.0. The mean post-test knowledge score percentage was 83.0. The mean post-test knowledge score percentage was higher than the pre-test knowledge score percentage thus implying that the self-instructional module increased the knowledge of staff nurses.Conclusion The study showed that the self-instructional module was effective in increasing the knowledge. Significant association of pre-test knowledge scores with selected demographic variables was noted.